The acquisition of failing companies in comparative law and, particularly, the colombian case - Quintero Serrano, Felipe (2016)
The acquisition of failing companies is a frequent practice in the modern commercial traffic. One of these modalities is to purchase companies immersed in an insolvency proceeding, either through the purchase of the operating business or the purchase of credits in order of its capitalization. The colombian regime insolvency has the tools to enable these type of operations although they do not achieved the desire objective.